Investigation of medical error-reporting system and reporting status in Iran in 2019 - Asaad Ranaei; Hasan Abolghasem Gorji; Aidin Aryankhesal; Mostafa Langarizadeh (Journal of Education and Health Promotion, 2020)
INTRODUCTION: Reporting medical errors is a major challenge in patient safety and improving service quality. The purpose of the present study is to investigate the status of error reporting and the challenges of developing an error-reporting system in Iran. METHODS: This study was designed with qualitative approach and grounded theory method in teaching hospitals affiliated to Iran University of Medical Sciences. The views of safety authorities at various levels of management, including those responsible for safety at the Ministry of Health, Vice Chancellor and Hospitals affiliated to Iran University of Medical Sciences, were investigated in 2019 regarding adverse events. RESULTS: Four major themes were identified included iceberg reporting and disclosure, weak reporting, underreporting, and non-error disclosure. The most common problems in reporting medical error were non-involvement of physicians in the error-reporting process, structural (human and information) bugs in root cause analysis sessions, and defective error prevention approaches designed based on the failure mode and effects analysis. DISCUSSION: Despite a large number of medical errors occurred in health-care settings, error reporting is still very low, with only a limited number of errors being reported routinely in hospitals and the rest are minor and occasional reports. CONCLUSION: Creating a mandatory error-reporting system and requiring physicians to report and participate in error analysis sessions can create a safety culture and increase the error-reporting rate.